Surface modified polymer dielectric film and preparation method and application of surface modified polymer dielectric film by utilizing pulling coating

By coating inorganic nanosheets using a lift coating process on the surface of the polymer dielectric film, the surface modified polymer dielectric film with a three-layer structure is solved, and the electrical breakdown problem of polymer dielectric materials under high field conditions is significantly improved, which significantly improves its electrical insulation performance and energy storage efficiency.

CN119955153APending Publication Date: 2025-05-09XI AN JIAOTONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510219664.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The prior art has challenges in improving the electrical insulation properties of polymer dielectric materials, especially under high-field conditions, the electrical breakdown mechanism has not been thoroughly analyzed, and the surface regulation method relies on experimental methods and lacks system design and optimization strategies.

Method used

The lift coating process is used to coat inorganic nanosheets on the surface of the polymer dielectric film to form a three-layer structure surface modified polymer dielectric film to reduce surface defects, improve charge injection barrier, and improve electrical insulation performance.

Benefits of technology

It significantly improves the breakdown strength and energy storage efficiency of polymer dielectric films, reduces conductivity loss, and achieves better electrical insulation performance. It also has simple process operation and low cost, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119955153A_ABST
    Figure CN119955153A_ABST
Patent Text Reader

Abstract

The invention discloses a surface-modified polymer dielectric film and a preparation method and application thereof by utilizing lifting coating, and belongs to the technical field of surface-modified polymer dielectric materials. The method comprises the following steps: adding an inorganic nanosheet into a solvent, carrying out ultrasonic dispersion, and adding an adhesive to prepare a suspension; and respectively coating the upper surface and the lower surface of a polymer with the turbid liquid by adopting a lifting coating process to form an upper coating layer and a lower coating layer, and then ventilating and drying to prepare the surface-modified polymer dielectric film. According to the method, the inorganic nanosheet coated polymer dielectric material with a three-layer structure is obtained by adopting a pulling coating process, the breakdown strength of the material can be greatly improved, the conductivity loss of the material is reduced, and the surface modified polymer dielectric film prepared by the method can improve the electrical insulation capability of the polymer dielectric film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface-modified polymer dielectric materials, and in particular relates to a surface-modified polymer dielectric film and a preparation method and application thereof by pulling and coating. Background Art

[0002] Electrostatic capacitors are widely used in modern power electronic systems. They are usually composed of two layers of metal electrodes and a dielectric material sandwiched between them. Polymer dielectric materials have significant advantages in electrostatic capacitor energy storage due to their high breakdown strength, low loss, good flexibility and self-cleaning ability.

[0003] In recent years, many researchers have conducted extensive research on the engineering design of polymer-nanomaterial composite structures in order to improve their insulation properties. With the emergence of a series of high-performance polymer-based dielectric materials, it is urgent to deeply understand the high-field aging and electrical breakdown mechanisms in order to apply these new materials in practice. However, since the high-field phenomenon in polymer dielectrics is affected by the complex interweaving of multiple factors, the current research on its electrical breakdown mechanism is still mainly at the phenomenological level and has not yet been deeply analyzed theoretically. Since the relationship between performance and structure in composite materials is more intuitive, some theoretical assumptions of electrical breakdown have been experimentally verified. For example, it is generally believed that when local traps are introduced into the polymer matrix and accumulate charges, the breakdown path will become longer. This assumption has been partially verified in inorganic nanoparticles (such as boron nitride) with higher breakdown strength. The conductivity of polymers depends not only on their bulk properties, but also on the interface properties, which determine how charges are injected from electrodes into polymer dielectrics.

[0004] An increasing number of experimental results have demonstrated that the use of inorganic coatings on surface-modified polymer films can provide good electrical insulation properties even under high-temperature operating conditions. These encouraging results demonstrate the importance of the surface when polymers are subjected to high voltages. However, current research in surface manipulation still relies mainly on experimental methods, and a systematic design and optimization strategy has not yet been formed.

[0005] The charge injection barrier height is theoretically defined as the difference between the work function of the metal electrode and the electron affinity of the dielectric polymer. However, experimental results show that the barrier height is almost unaffected by the work function of the metal electrode. Surface defects are a reasonable explanation for this phenomenon. Surface defects are common in all polymers and other solid dielectrics. These defects introduce defect energy levels between the conduction band and the valence band when the electrodes are in contact. When a bias voltage is applied, these surface defects can promote the injection of charge carriers from the electrode and their transition to the conduction band of the polymer. This multi-stage transition process effectively reduces the difficulty of electron transition, thereby significantly reducing the charge injection barrier height.

[0006] Therefore, studying how to reduce surface defects through surface modification to improve the electrical insulation properties of polymer dielectrics has become an important direction in current dielectric material research.

[0007] Currently, an improved method is to use chemical vapor deposition technology to coat nanosheets with wide band gaps on the surface of polymers. However, chemical vapor deposition technology requires high material costs and cumbersome processing steps, making it difficult to achieve large-scale manufacturing. Another existing technology uses a spray coating method to spray two-dimensional materials, but due to the limited area of ​​one spray, it is difficult to make the coating layer uniform in large-area spraying, and it is difficult to control the orientation of inorganic nanosheets in the spraying process, which will reduce the performance of the final product and make it difficult to achieve large-scale production. Summary of the invention

[0008] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a surface-modified polymer dielectric film and a preparation method and application thereof using pull-up coating. The method adopts a pull-up coating process to obtain an inorganic nanosheet-coated polymer dielectric material with a three-layer structure, which can greatly improve the breakdown strength of the material and reduce the electrical conductivity loss of the material. The surface-modified polymer dielectric film prepared by this method can improve the electrical insulation capability of the polymer dielectric film.

[0009] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a surface-modified polymer dielectric film by using pull-coating, comprising the following steps: The inorganic nanosheets are added into a solvent and ultrasonically dispersed, and then a binder is added to prepare a suspension; The suspension is coated on the upper surface and the lower surface of the polymer respectively to form an upper coating layer and a lower coating layer by using a pull-up coating process, and then the coating is dried by ventilation to obtain a surface-modified polymer dielectric film.

[0010] In one embodiment, the solvent is a mixed solvent of toluene and ethanol; the mass ratio of toluene to ethanol is 1.5:1.

[0011] In one embodiment, the mass ratio of the inorganic nanosheets to the binder is 1:1.

[0012] In one embodiment, the mass fraction of the solid content in the suspension is 1.3-4%.

[0013] In one embodiment, the inorganic nanosheet is any one of boron nitride, hafnium oxide, aluminum oxide, and montmorillonite sheets; the adhesive is polyvinyl alcohol or polyvinyl butyral; the polymer is polyimide, polyetherimide, polypropylene, polyethylene, polyvinylidene fluoride, polyvinylidene fluoride copolymer, polycarbonate, polyamide-imide or epoxy resin.

[0014] In one embodiment, the pulling coating time is 30 to 60 seconds; the ventilation drying temperature is 80° C., and the ventilation drying time is 12 to 24 hours.

[0015] The present invention also provides a surface-modified polymer dielectric film prepared by the above-mentioned method for preparing a surface-modified polymer dielectric film by pulling coating, wherein the surface-modified polymer dielectric film uses a polymer as a base material, and the upper coating layer and the lower coating layer are respectively coated on the upper surface and the lower surface of the base material.

[0016] In one embodiment, the overall thickness of the surface-modified polymer dielectric film is 8-12 microns; the thickness of the upper coating layer and the lower coating layer are equal, and the thickness of the upper coating layer and the lower coating layer are both 0.15-2 microns.

[0017] In one embodiment, at a field strength of 300 MV / m, the energy storage efficiency of the surface modified polymer dielectric film is 79.8-91.3%, and the loss is 0.19-0.57 J / cm 3 ; The breakdown strength is 616~642MV / m.

[0018] In another aspect, the present invention also provides a use of a surface-modified polymer dielectric film prepared by the above-mentioned method for preparing a surface-modified polymer dielectric film by pulling and coating in a dielectric energy storage material.

[0019] Compared with the prior art, the present invention has the following beneficial effects: On one hand, the present invention provides a method for preparing a surface-modified polymer dielectric film by using a pull-up coating, wherein the method performs surface modification on the polymer dielectric film, and the coating of inorganic nanosheets can form a uniform protective layer on the surface of the polymer film, reduce surface defects, increase the charge injection barrier, and improve its electrical insulation performance. The present invention uses a pull-up coating process to ensure the uniformity of the coating layer and the high orientation of the two-dimensional inorganic nanosheets on a large area of ​​the polymer film. The method is simple to operate, low in cost, widely applicable, and conducive to large-scale production.

[0020] The coating process used in this preparation method is a Czochralski coating process. Compared with chemical vapor deposition (CVD), physical vapor deposition (PVD), atomic layer deposition (ALD) and other processes that require strict experimental conditions and high production costs, the Czochralski coating process is simple to operate, low cost, requires simple and easy-to-process raw materials, has a short preparation cycle, and has high repeatability. It has great advantages in industrial production. More importantly, compared with the spraying process, the Czochralski coating process can ensure the uniformity of the coating layer and the high orientation of the two-dimensional inorganic nanosheets on a large area of ​​polymer film.

[0021] On the other hand, the present invention provides a surface-modified polymer dielectric film prepared by the above-mentioned pulling coating preparation method. The surface-modified polymer dielectric film has a three-layer structure of upper, middle and lower layers. The upper and lower layers are uniform coating layers, and the middle layer is a polymer matrix. The surface-modified polymer dielectric film significantly reduces the surface defect density of the material, improves the breakdown strength, and reduces the conductivity loss.

[0022] Furthermore, the thickness of the coating layer has an important influence on the insulating properties of the polymer dielectric material. When the coating layer is of moderate thickness, it can cover and fill surface defects and improve the electrical insulation properties of the dielectric material. However, if the coating layer is too thin, it cannot completely cover the surface defects and cannot fully exert the advantages of surface modification; on the contrary, a coating layer that is too thick will introduce new interface or internal defects, especially at the interface between the coating layer and the polymer matrix, where interface defects may be formed, affecting the electrical insulation properties of the polymer dielectric material. The present invention controls the thickness of the coating layer of the surface-modified polymer dielectric film provided by the present invention by adjusting the solid content of the inorganic nanosheets and the adhesive in the suspension. The energy storage efficiency of the surface-modified polymer dielectric film finally obtained can be as high as 79.8~91.3% at a field strength of 300MV / m, and the loss is only 0.19~0.57J / cm 3 ; The breakdown strength is 616~642MV / m.

[0023] Due to its excellent properties, this material shows broad application potential in the field of dielectric energy storage materials. It can be used in electric vehicles, aerospace, photovoltaic grid-connected and other fields, and has good development prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a SEM image of the surface modified polymer dielectric film sample provided by the present invention; Figure 2 A comparison chart of energy storage density data of the surface modified polymer dielectric film sample and the polyimide matrix prepared by the present invention; Figure 3It is a comparison diagram of the Weibull distribution of the breakdown strength of the surface modified polymer dielectric film sample prepared by the present invention and the polyimide matrix; Figure 4 It is a loss comparison diagram of the surface modified polymer dielectric film sample prepared by the present invention and the polyimide matrix. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0030] The starting point of the structural design of the surface-modified polymer dielectric film provided by the present invention is that the research of the applicant's research group found that surface defects in the polymer will introduce defect energy levels between the conduction band and the valence band, reduce the charge injection barrier, and thus reduce the electrical insulation performance of the material. In order to solve this problem, the surface of the polymer dielectric film is modified by pulling and coating on the surface of the polymer film, and inorganic nanosheets are coated, which helps to reduce surface defects and improve electrical insulation performance.

[0031] In one aspect, the present invention provides a method for surface modification of a polymer dielectric film by using pull-coating, comprising the following steps: Step 1: Weigh a certain amount of inorganic nanosheets, add them to a mixed solvent, and disperse them in the solvent by ultrasound, add a binder, stir to dissolve the binder, and obtain a suspension; wherein the mass ratio of the inorganic nanosheets to the binder in the suspension is 1:1, and the mass fraction of the solid content (the total mass of the inorganic nanosheets and the binder) in the suspension is 1.3-4%. The present invention controls the viscosity of the suspension by changing the solid content of the inorganic nanosheets and the binder in the suspension, thereby controlling the thickness of the coating layer of the surface-modified polymer dielectric film provided by the present invention.

[0032] Step 2: Use a pull-up coating process to coat the suspension on the upper and lower surfaces of the base material (polymer) to form an upper coating layer and a lower coating layer, and then ventilate and dry to obtain a dense surface-modified polymer dielectric film with high insulation performance. The surface-modified polymer dielectric film has a three-layer structure consisting of an upper coating layer, a polymer and a lower coating layer.

[0033] Wherein, the polymer is polyimide, polyetherimide, polypropylene, polyethylene, polyvinylidene fluoride, polyvinylidene fluoride copolymer, polycarbonate, polyamide-imide or epoxy resin.

[0034] Wherein, the inorganic nanosheets are boron nitride, hafnium oxide, aluminum oxide or montmorillonite sheets.

[0035] The binder is polyvinyl alcohol or polyvinyl butyral. Since the inorganic nanosheets have low adhesion and are easily detached from the surface of the polymer dielectric film, the binder is added to improve the surface wettability of the polymer dielectric film, so that the inorganic nanosheets can be better attached to the surface of the polymer dielectric film.

[0036] The solvent used above is a mixed solvent of toluene and ethanol; the mass ratio of toluene to ethanol is 1.5:1. In a specific implementation process, the mass of toluene is 46.08 g, and the mass of ethanol is 30.72 g.

[0037] In a specific implementation process, when the mass fraction of the solid content in the suspension is 1.5%, the energy storage density of the prepared surface modified polymer dielectric film is as high as 91.3%.

[0038] In a specific implementation process, in step one, the adhesive is dissolved in the solvent by stirring at a temperature of 25-40°C; in step two, the pulling and coating time used is 30-60s; the ventilation drying temperature is 80°C, and the ventilation drying time is 12-24h.

[0039] Another aspect of the present invention provides a surface-modified polymer dielectric film obtained by a method for surface-modifying a polymer dielectric film by pull-coating, wherein a polymer is used as a base material, and an upper coating layer and a lower coating layer are coated on the upper and lower surfaces of the base material by pull-coating, respectively; the upper coating layer and the lower coating layer are made of inorganic nanosheets and an adhesive. The surface-modified polymer dielectric film uses inorganic nanosheets to reduce surface defects of the polymer film, so as to improve the electrical insulation performance of the surface-modified polymer dielectric film.

[0040] The overall thickness of the surface-modified polymer dielectric film is 8-12 microns; the thickness of the upper coating layer and the lower coating layer are both 0.15-2 microns.

[0041] According to the test, under the field strength of 300MV / m, the energy storage efficiency of the surface modified polymer dielectric film prepared by the present invention is 79.8-91.3%, and the loss is 0.19-0.57J / cm 3 ; The breakdown strength is 616~642MV / m.

[0042] In one aspect, the present invention uses a surface-modified polymer dielectric film obtained by a method for surface-modifying a polymer dielectric film by pull-coating in a dielectric energy storage material.

[0043] In one embodiment, a polyimide dielectric polymer is used as a matrix material, an inorganic nanosheet is used as a coating layer, and a three-layer structure of upper, middle and lower layers is formed, wherein the upper and lower layers are coating layers, and the middle layer is a polymer matrix; a suspension having different solid contents is coated on the upper and lower surfaces of the polymer to form a three-layer structure. The mass fraction of the solid content in the suspension is 1.3-4%, the overall thickness of the material is 8-12 microns, and the thickness of the upper and lower coating layers is 0.15-2 microns.

[0044] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0045] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0046] In addition, the specific calculation method of the energy storage efficiency mentioned in the present invention is as follows: The discharge energy density of film capacitors can be calculated by the following formula: , for linear dielectric materials, the discharge energy density can be simplified to: Since part of the stored energy cannot be released immediately, the discharge energy density (U d ) and the energy density stored during charging (U c ) is taken as the energy storage efficiency (η), and its expression is: η= .

[0047] Example 1 On the one hand, this embodiment provides a method for preparing a surface-modified polymer dielectric film by using pull-coating, which is as follows: 1) Weigh 0.5 g of MMT nanopowder into a beaker, add 30.72 g of ethanol and 46.08 g of toluene, add 0.5 g of PVB after needle ultrasonic treatment for 1 hour, stir at room temperature until completely dissolved, and ultrasonicate for another 30 minutes before coating to obtain the suspension required for coating.

[0048] 2) The static electricity on the surface of the PI Kapton film was washed off in ethanol and dried under ventilation at 80°C for 10 minutes. The suspension was coated on both sides of the PI Kapton film using a pull-up coating process with a dipping time of 60 seconds, and then dried under ventilation at 80°C for 12 hours to obtain a surface-modified polymer dielectric film.

[0049] In this embodiment, polyimide (PI Kapton) is used as the polymer layer, and a coating layer composed of two-dimensional montmorillonite (2D MMT) nanosheets (model APA) and polyvinyl butyral (PVB) is used as the upper coating layer and the lower coating layer.

[0050] The solid content of the suspension used for the surface-modified polymer dielectric film in this embodiment is 1.3%. The overall thickness of the three-layer film is 8 microns, of which the thickness of the upper coating layer is 0.15 microns and the thickness of the lower coating layer is 0.15 microns.

[0051] The present invention adopts HCWP-3000 high temperature dielectric and IV test system to test the energy storage efficiency of the material, and the test AC electric field frequency is 10HZ.

[0052] The relevant energy storage properties of the surface modified polymer dielectric film in Example 1 are as follows Figure 2 Middle (a), Figure 3 (a) and Figure 4As shown in (a), the performance of the surface-modified polymer dielectric film reaches the following indicators: at a field strength of 300 MV / m, the energy storage efficiency is 85.2% and the loss is 0.39 J / cm 3 . The breakdown strength is 642MV / m.

[0053] Example 2 On the one hand, this embodiment provides a method for preparing a surface-modified polymer dielectric film by using pull-coating, which is as follows: 1) Weigh 0.6 g of MMT nanopowder into a beaker, add 30.72 g of ethanol and 46.08 g of toluene, add 0.6 g of PVB after needle ultrasonication for 1 hour, stir at room temperature until completely dissolved, and ultrasonicate for another 30 minutes before coating to obtain the suspension required for coating.

[0054] 2) The static electricity on the surface of the PI Kapton film was washed off in ethanol and dried under ventilation at 80°C for 10 minutes. The suspension was coated on both sides of the PI Kapton film using a pull-up coating process with a dipping time of 30 seconds, and then dried under ventilation at 80°C for 24 hours to obtain a surface-modified polymer dielectric film.

[0055] In this embodiment, polyimide (PI Kapton) is used as the polymer layer, and two-dimensional montmorillonite (2D MMT) nanosheets (model APA) and polyvinyl butyral (PVB) are used as the upper coating layer and the lower coating layer.

[0056] The solid content of the suspension used for the surface-modified polymer dielectric film in this embodiment is 1.5%. The overall thickness of the three-layer film is 8 microns, of which the thickness of the upper coating layer is 0.2 microns and the thickness of the lower coating layer is 0.2 microns.

[0057] The present invention adopts HCWP-3000 high temperature dielectric and IV test system to test the energy storage efficiency of the material, and the test AC electric field frequency is 10HZ.

[0058] The cross-sectional morphology of the surface modified polymer dielectric film in Example 2 is as follows: Figure 1 (b) shows that the relevant energy storage performance is Figure 2 (b) and Figure 4 As shown in (b), the performance of the surface-modified polymer dielectric film reaches the following indicators: at a field strength of 300 MV / m, the energy storage efficiency is 91.3% and the loss is 0.19 J / cm 3 .

[0059] See also Figure 2 and Figure 4 As shown, when it is at 1.5%, it is at the peak and the product effect is the best.

[0060] Example 3 On the one hand, this embodiment provides a method for preparing a surface-modified polymer dielectric film by using pull-coating, which is as follows: 1) Weigh 0.7 g of MMT nanopowder into a beaker, add 30.72 g of ethanol and 46.08 g of toluene, add 0.7 g of PVB after needle ultrasonication for 1 hour, stir at room temperature until completely dissolved, and ultrasonicate for another 30 minutes before coating to obtain the suspension required for coating.

[0061] 2) The static electricity on the surface of the PI Kapton film was washed off in ethanol and dried under ventilation at 80°C for 10 minutes. The suspension was coated on both sides of the PI Kapton film using a pull-up coating process with a dipping time of 30 seconds, and then dried under ventilation at 80°C for 24 hours to obtain a surface-modified polymer dielectric film.

[0062] In this embodiment, polyimide (PI Kapton) is used as the polymer layer, and two-dimensional montmorillonite (2D MMT) nanosheets (model APA) and polyvinyl butyral (PVB) are used as the upper coating layer and the lower coating layer.

[0063] The solid content of the suspension used for the surface-modified polymer dielectric film in this embodiment is 1.8%. The overall thickness of the three-layer film is 9 microns, of which the thickness of the upper coating layer is 0.5 microns and the thickness of the lower coating layer is 0.5 microns.

[0064] The present invention adopts HCWP-3000 high temperature dielectric and IV test system to test the energy storage efficiency of the material, and the test AC electric field frequency is 10HZ.

[0065] The relevant energy storage properties of the surface modified polymer dielectric film in Example 3 are as follows: Figure 2 (c) and Figure 4 As shown in (c), the performance of the surface-modified polymer dielectric film reaches the following indicators: at a field strength of 300MV / m, the energy storage efficiency is 86.9% and the loss is 0.32J / cm 3 .

[0066] Example 4 On the one hand, this embodiment provides a method for preparing a surface-modified polymer dielectric film by using pull-coating, which is as follows: 1) Weigh 0.75 g of MMT nanopowder into a beaker, add 30.72 g of ethanol and 46.08 g of toluene, add 0.75 g of PVB after needle ultrasonication for 1 hour, stir at room temperature until completely dissolved, and ultrasonicate for another 30 minutes before coating to obtain the suspension required for coating.

[0067] 2) The static electricity on the surface of the PI Kapton film was washed off in ethanol and dried under ventilation at 80°C for 10 minutes. The suspension was coated on both sides of the PI Kapton film using a pull-up coating process with a dipping time of 30 seconds, and then dried under ventilation at 80°C for 24 hours to obtain a surface-modified polymer dielectric film.

[0068] In this embodiment, polyimide (PI Kapton) is used as the polymer layer, and two-dimensional montmorillonite (2D MMT) nanosheets (model APA) and polyvinyl butyral (PVB) are used as the upper coating layer and the lower coating layer.

[0069] The solid content of the suspension used for the surface-modified polymer dielectric film in this embodiment is 1.9%. The overall thickness of the three-layer film is 9 microns, of which the thickness of the upper coating layer is 0.7 microns and the thickness of the lower coating layer is 0.7 microns.

[0070] The present invention adopts HCWP-3000 high temperature dielectric and IV test system to test the energy storage efficiency of the material, and the test AC electric field frequency is 10HZ.

[0071] The relevant energy storage properties of the surface modified polymer dielectric film in Example 4 are as follows: Figure 2 Middle (d) and Figure 4 As shown in (d), the performance of the surface-modified polymer dielectric film reaches the following indicators: at a field strength of 300 MV / m, the energy storage efficiency is 85.2% and the loss is 0.44 J / cm 3 .

[0072] Example 5 On the one hand, this embodiment provides a method for preparing a surface-modified polymer dielectric film by using pull-coating, which is as follows: 1) Weigh 0.8 g of MMT nanopowder into a beaker, add 30.72 g of ethanol and 46.08 g of toluene, add 0.8 g of PVB after needle ultrasonic treatment for 1 hour, stir at room temperature until completely dissolved, and ultrasonicate for another 30 minutes before coating to obtain the suspension required for coating.

[0073] 2) The static electricity on the surface of the PI Kapton film was washed off in ethanol and dried under ventilation at 80°C for 10 minutes. The suspension was coated on both sides of the PI Kapton film using a pull-up coating process with a dipping time of 30 seconds, and then dried under ventilation at 80°C for 24 hours to obtain a surface-modified polymer dielectric film.

[0074] In this embodiment, polyimide (PI Kapton) is used as the polymer layer, and two-dimensional montmorillonite (2D MMT) nanosheets (model APA) and polyvinyl butyral (PVB) are used as the upper coating layer and the lower coating layer.

[0075] The solid content of the suspension used for the surface-modified polymer dielectric film in this embodiment is 2%. The overall thickness of the three-layer film is 10 microns, of which the thickness of the upper coating layer is 1 micron and the thickness of the lower coating layer is 1 micron.

[0076] The present invention adopts HCWP-3000 high temperature dielectric and IV test system to test the energy storage efficiency of the material, and the test AC electric field frequency is 10HZ.

[0077] The relevant energy storage properties of the surface modified polymer dielectric film in Example 5 are as follows: Figure 2 Middle (e), Figure 3 (b) and Figure 4 As shown in (e), the performance of the surface-modified polymer dielectric film reaches the following indicators: at a field strength of 300 MV / m, the energy storage efficiency is 79.8% and the loss is 0.57 J / cm 3 . The breakdown strength is 616MV / m.

[0078] Example 6 On the one hand, this embodiment provides a method for preparing a surface-modified polymer dielectric film by using pull-coating, which is as follows: 1) Weigh 1g of MMT nanopowder into a beaker, add 30.72g of ethanol and 46.08g of toluene, add 1g of PVB after needle ultrasonication for 1 hour, stir at room temperature until completely dissolved, and ultrasonicate for another 30 minutes before coating to obtain the suspension required for coating.

[0079] 2) The static electricity on the surface of the PI Kapton film was washed off in ethanol and dried under ventilation at 80°C for 10 minutes. The suspension was coated on both sides of the PI Kapton film using a pull-up coating process with a dipping time of 30 seconds, and then dried under ventilation at 80°C for 24 hours to obtain a surface-modified polymer dielectric film.

[0080] In this embodiment, polyimide (PI Kapton) is used as the polymer layer, and two-dimensional montmorillonite (2D MMT) nanosheets (model APA) and polyvinyl butyral (PVB) are used as the upper coating layer and the lower coating layer.

[0081] The solid content of the suspension used for the surface-modified polymer dielectric film in this embodiment is 2.5%. The overall thickness of the three-layer film is 10 microns, of which the thickness of the upper coating layer is 1.4 microns and the thickness of the lower coating layer is 1.4 microns.

[0082] The present invention adopts HCWP-3000 high temperature dielectric and IV test system to test the energy storage efficiency of the material, and the test AC electric field frequency is 10HZ.

[0083] The relevant energy storage properties of the surface modified polymer dielectric film in Example 6 are as follows: Figure 2 Middle (f) and Figure 4 As shown in (f), the performance of the surface-modified polymer dielectric film reaches the following indicators: at a field strength of 300 MV / m, the energy storage efficiency is 81.5% and the loss is 0.54 J / cm 3 .

[0084] Example 7 On the one hand, this embodiment provides a method for preparing a surface-modified polymer dielectric film by using pull-coating, which is as follows: 1) Weigh 1.6 g of MMT nanopowder into a beaker, add 30.72 g of ethanol and 46.08 g of toluene, add 1.6 g of PVB after needle ultrasonication for 1 hour, stir at room temperature until completely dissolved, and ultrasonicate for another 30 minutes before coating to obtain the suspension required for coating.

[0085] 2) The static electricity on the surface of the PI Kapton film was washed off in ethanol and dried under ventilation at 80°C for 10 minutes. The suspension was coated on both sides of the PI Kapton film using a pull-up coating process with a dipping time of 30 seconds, and then dried under ventilation at 80°C for 24 hours to obtain a surface-modified polymer dielectric film.

[0086] In this embodiment, polyimide (PI Kapton) is used as the polymer layer, and two-dimensional montmorillonite (2D MMT) nanosheets (model APA) and polyvinyl butyral (PVB) are used as the upper coating layer and the lower coating layer.

[0087] The solid content of the suspension used for the surface-modified polymer dielectric film in this embodiment is 4%. The overall thickness of the three-layer film is 12 microns, of which the thickness of the upper coating layer is 2 microns and the thickness of the lower coating layer is 2 microns.

[0088] The present invention adopts HCWP-3000 high temperature dielectric and IV test system to test the energy storage efficiency of the material, and the test AC electric field frequency is 10HZ.

[0089] The surface morphology of the surface-modified polymer dielectric film in Example 7 is as follows: Figure 1 (a) shows that the relevant energy storage performance is Figure 2 Medium (g) and Figure 4 As shown in (g), the performance of the surface-modified polymer dielectric film reaches the following indicators: at a field strength of 300MV / m, the energy storage efficiency is 84.5% and the loss is 0.42J / cm 3 .

[0090] By comparing Examples 1-7, it can be seen that the structure of the surface-modified polymer dielectric film by pulling and coating can make the surface-modified polymer dielectric film have a higher energy storage efficiency of 79.8-91.3% and a lower loss of 0.19-0.57 J / cm under an electric field of 300 MV / m. 3 . And it has a high breakdown strength of 616~642MV / m. In addition, it should be pointed out that according to the technical solution of the present invention, many more embodiments can be cited above. According to a large number of experimental results of the applicant, the purpose of the present invention can be achieved within the scope of the claims of the present invention.

[0091] The invention of the present invention is to provide a method for surface modification of polymer dielectric film by using pull-coating, which is based on the design of pull-coating polymer dielectric film, takes polymer as matrix material, and pulls and coats inorganic nanosheets and adhesives with different mass fractions in suspension onto the surface of polymer matrix. The present invention not only reduces polymer surface defects and improves charge injection barrier through surface modification, so as to improve its electrical insulation performance, but also uses the coating method of pull-coating, which can ensure the uniformity of coating layer and high orientation of two-dimensional inorganic nanosheets on large-area polymer film; the operation is simple, the cost is low, and it is conducive to large-scale manufacturing.

[0092] The surface modified polymer dielectric film prepared by the method has an energy storage efficiency as high as 91.3% and a low energy density as low as 0.19 J / cm 3 The excellent properties of the surface-modified polymer dielectric film make it applicable to hybrid vehicles, aerospace, photovoltaic grid-connected, oil and gas exploration and other fields.

[0093] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a surface-modified polymer dielectric film by pulling coating, characterized in that: The following steps are involved: The inorganic nanosheets are added into a solvent and ultrasonically dispersed, and then a binder is added to prepare a suspension; The suspension is coated on the upper surface and the lower surface of the polymer respectively to form an upper coating layer and a lower coating layer by using a pull-up coating process, and then the coating is dried by ventilation to obtain a surface-modified polymer dielectric film.

2. The method for preparing a surface-modified polymer dielectric film by pulling coating according to claim 1, characterized in that: The solvent is a mixed solvent of toluene and ethanol; the mass ratio of toluene to ethanol is 1.5:

1.

3. The method for preparing a surface-modified polymer dielectric film by pulling coating according to claim 1, characterized in that: The mass ratio of the inorganic nanosheets to the binder is 1:

1.

4. The method for preparing a surface-modified polymer dielectric film by pulling coating according to claim 1, characterized in that: The mass fraction of solid content in the suspension is 1.3-4%.

5. The method for preparing a surface-modified polymer dielectric film by pulling coating according to claim 1, characterized in that: The inorganic nanosheet is any one of boron nitride, hafnium oxide, aluminum oxide, and montmorillonite sheets; the adhesive is polyvinyl alcohol or polyvinyl butyral; the polymer is polyimide, polyetherimide, polypropylene, polyethylene, polyvinylidene fluoride, polyvinylidene fluoride copolymer, polycarbonate, polyamide-imide, or epoxy resin.

6. The method for preparing a surface-modified polymer dielectric film by pulling coating according to claim 1, characterized in that: The pulling coating time is 30 to 60 seconds; the ventilation drying temperature is 80° C., and the ventilation drying time is 12 to 24 hours.

7. A surface-modified polymer dielectric film obtained by the method for preparing a surface-modified polymer dielectric film by pulling coating according to any one of claims 1 to 6, characterized in that: The surface-modified polymer dielectric film uses polymer as a base material, and the upper coating layer and the lower coating layer are coated on the upper surface and the lower surface of the base material respectively.

8. The surface-modified polymer dielectric film according to claim 7, characterized in that: The overall thickness of the surface modified polymer dielectric film is 8-12 microns; the thickness of the upper coating layer and the lower coating layer are equal, and the thickness of the upper coating layer and the lower coating layer are both 0.15-2 microns.

9. The surface-modified polymer dielectric film according to claim 7, characterized in that: At a field strength of 300 MV / m, the energy storage efficiency of the surface-modified polymer dielectric film is 79.8-91.3%, and the loss is 0.19-0.57 J / cm 3 ; The breakdown strength is 616~642MV / m.

10. Use of a surface-modified polymer dielectric film obtained by the method for preparing a surface-modified polymer dielectric film by pulling coating according to any one of claims 1 to 6 in dielectric energy storage materials.

Citation Information

Cited By

  • Double-layer nanometer coating polymer dielectric film based on charge blocking and dissipation cooperative regulation and control and preparation method of double-layer nanometer coating polymer dielectric film

    CN122483381A